Effect of Antioxidants in Medicinal Products on Intestinal Drug Transporters - Chetan P. Kulkarni; Jia Yang; Megan L. Koleske; Giovanni Lara; Khondoker Alam; Andre Raw; Bhagwant Rege; Liang Zhao; Dongmei Lu; Lei Zhang; Lawrence X. Yu; Robert A. Lionberger; et al. (MDPI AG, 2024)
The presence of mutagenic and carcinogenic N-nitrosamine impurities in medicinal products poses a safety risk. While incorporating antioxidants in formulations is a potential mitigation strategy, concerns arise regarding their interference with drug absorption by inhibiting intestinal drug transporters. Our study screened thirty antioxidants for inhibitory effects on key intestinal transporters-OATP2B1, P-gp, and BCRP in HEK-293 cells (OATP2B1) or membrane vesicles (P-gp, BCRP) using 3H-estrone sulfate, 3H-N-methyl quinidine, and 3H-CCK8 as substrates, respectively. The screen identified that butylated hydroxyanisole (BHA) and carnosic acid inhibited all three transporters (OATP2B1, P-gp, and BCRP), while ascorbyl palmitate (AP) inhibited OATP2B1 by more than 50%. BHA had IC50 values of 71 ± 20 µM, 206 ± 14 µM, and 182 ± 49 µM for OATP2B1, BCRP, and P-gp, respectively. AP exhibited IC50 values of 23 ± 10 µM for OATP2B1. The potency of AP and BHA was tested with valsartan, an OATP2B1 substrate, and revealed IC50 values of 26 ± 17 µM and 19 ± 11 µM, respectively, in HEK-293-OATP2B1 cells. Comparing IC50 values of AP and BHA with estimated intestinal concentrations suggests an unlikely inhibition of intestinal transporters at clinical concentrations of drugs formulated with antioxidants.